Attitude Variability Among Latin American Publics: How Party System Structuration Affects Left/Right Ideology - Harbers, Imke; Steenbergen, Marco; de Vries, Catherine (Sage Journals, 2012)
Political scientists often describe party competition, political behavior or public preferences in left/right terms. Nevertheless, the usefulness of the concepts “left” or “right” is rarely explored. This study assesses whether the left/right continuum resonates with publics in developing Latin American democracies. Using data from the 2008 wave of the Latin American Public Opinion Project (LAPOP), the authors measure variability in left/right self-placement in three Latin American countries, namely, Ecuador, Mexico, and Chile. Building on the approach developed by Alvarez and Brehm for public opinion in the United States, the authors explore (a) the extent to which voters in Ecuador, Mexico, and Chile possess predicable left/right positions and (b) whether predictability can be attributed to individual- and country-level characteristics. At the individual level, the authors show that variability decreases with political sophistication. At the country level, they find that a lower degree of programmatic party system structuration leads to higher levels of response variation. Mapping the variability in left/right preferences provides important insights into the structure of public opinion and contours of political behavior in Latin America and how they differ from those of other regions such as North America. In addition, this study brings to bear important new individual-level insights into recent political developments in the Latin American region, especially the so-called left turn in Latin American politics.
Keywords: 59 Ciencia Política::5910 Opinión pública; ODS 10 - Reducción de las desigualdades; ODS 16 - Paz, justicia e instituciones sólidas